Dimensions of Growth? Examining the Distinctiveness of the Five Factors of the Posttraumatic Growth Inventory. Issue 3 (29th June 2018) - Silverstein, Madison W.; Witte, Tracy K.; Lee, Daniel J.; Kramer, Lindsay B.; Weathers, Frank W.
Abstract: Posttraumatic growth, defined as positive transformation following trauma, is commonly measured using the Posttraumatic Growth Inventory (PTGI; Tedeschi & Calhoun, 1996) and is postulated to comprise five distinct domains: Changes in Relationships, Life Possibilities, Personal Strength, Spirituality, and Appreciation of Life. However, research has indicated that the model fit is not good and the factors are highly intercorrelated. Further, no studies have formally examined the heterogeneity of correlations of the five factors with external constructs. In an effort to examine the construct validity of the five‐factor model of the PTGI, the present study aimed to examine the degree to which the theorized five factors demonstrate meaningful differential associations with relevant external correlates. Participants were 400 undergraduate students who reported having experienced a stressful event and completed the Life Events Checklist for DSM‐5, PTGI, Posttraumatic Stress Disorder Checklist for DSM‐5, Grit Scale‐12, Connor‐Davidson Resilience Scale‐10, and Work and Social Adjustment Scale. We found few instances of significant differentiation, and effect sizes for pairwise comparisons were generally small, Cohen's q s = 0.01–0.35. Although factor analytic evidence suggests there are five distinct underlying constructs, our results indicated that these factors do not significantly differ in their associations with external correlates. Implications for use of the PTGI and future research directions are discussed.